Anthropic pressure drives resource selection of an adaptable generalist in human‐dominated landscapes - Markus Handschuh; Peter Linderoth; Janosch Arnold; Ilse Storch; Manisha Bhardwaj (Conservation Science and Practice, 2024)
Abstract Few landscapes on earth remain free of human‐modification, which may influence resource selection in wildlife. To investigate the effects of anthropic pressure on wild boar (Sus scrofa) and explore management implications, we studied how diel resource selection of the species' main life stages changed with spatial variations of human access (e.g., for recreation), temporal changes in hunting pressure, and habitat type. Using 206,461 hourly GPS‐locations of 15 males, 11 females with dependent young, and 17 other females from south‐western Germany, we found anthropic pressure influenced resource selection more than ecological factors. All boars were more likely to select for low human‐access areas than high human‐access areas, regardless of habitat. Hunting pressure was most avoided by females with dependent piglets, followed by males and other females. Since both hunting activity and general human access affected resource selection, they should be considered simultaneously in wildlife management and conservation. We suggest the further establishment of wildlife reserves that are inaccessible to people where boar may remain more localized, thereby reducing the risk of disease transmission, and boar hunting to focus on open lands and refuge boundaries to reduce crop damage. This may also benefit overall human‐wildlife coexistence, animal welfare, and biodiversity conservation in anthropized environments.